A Multi-Faceted Literature Review of Challenges in Iran’s Knowledge-Based ICT Firms - Fotoohi, Arezoo (Fakultas Ekonomi Universitas Andalas, 2024)
This review paper examines the multifaceted growth challenges faced by Knowledge-Based Firms (KBFs) operating in Information and Communication Technology (ICT) firms in Iran. Through a comprehensive analysis, the study identifies critical barriers across several domains, including financial constraints, market development limitations, political, regulatory, and legal complexities, business model intricacies, and knowledge-based law enforcement issues. Unlike previous studies that typically focus on isolated factors, this research offers a holistic view of the obstacles impeding the growth of ICT firms within the specific context of Iran and its regulatory environment. Key findings reveal that financial challenges are compounded by limited access to high-quality equipment and skilled personnel, while market development is hindered by both domestic and international barriers. Regulatory and legal hurdles, including inadequate intellectual property protections and cumbersome administrative processes, further exacerbate these issues. The study also highlights the need for strategic reforms in policy frameworks, enhanced coordination among governmental bodies, and targeted support mechanisms to address the evolving needs of these enterprises. Based on the analysis, the paper proposes several policy recommendations aimed at fostering an environment conducive to the sustainable growth and innovation of Iran’s ICT sector. These include optimizing tax policies, facilitating international market entry, revising regulatory frameworks, and improving support for knowledge-based law enforcement. The findings highlight the importance of a nuanced and adaptive approach to policy-making to ensure the competitiveness and resilience of ICT companies in Iran's dynamic economic landscape.